2020
DOI: 10.1101/2020.09.06.284588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type II collagen-positive progenitors are major stem cells to control skeleton development and vascular formation

Abstract: Previous studies have revealed that type II collagen positive (Col2+) cells represent a kind of skeleton stem cells (SSC) and their descendants contribute to chondrocytes, osteoblasts, Cxcl12 (chemokine (C-X-C motif) ligand 12)-abundant stromal cells and bone marrow stromal/mesenchymal progenitor cells in postnatal life. To further elucidate the function of Col2+ progenitors, we generated mice with ablation of either embryonic or postnatal Col2+ cells. Embryonic ablation of Col2+ progenitors caused the mouse d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In this way, although it is generally assumed that a long bone is formed by endochondral ossification, much of its postnatal ossification occurs subperiosteally and so is essentially intramembranous [ 8 ]. Additionally, a combination of both intramembranous and endochondral ossification has been reported to occur simultaneously during craniofacial bone development [ 9 ], clavicle formation [ 10 ], fracture healing of mandible [ 11 ], and bone lengthening through callus distraction [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, although it is generally assumed that a long bone is formed by endochondral ossification, much of its postnatal ossification occurs subperiosteally and so is essentially intramembranous [ 8 ]. Additionally, a combination of both intramembranous and endochondral ossification has been reported to occur simultaneously during craniofacial bone development [ 9 ], clavicle formation [ 10 ], fracture healing of mandible [ 11 ], and bone lengthening through callus distraction [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intramembranous and endochondral ossification are usually considered as separate modes of ossification; however, this is a simplification, since it has been reported that both occur simultaneously during the development of many bones [ 9 , 10 ]. Furthermore, although it is assumed that long bones are formed by endochondral ossification, much of their postnatal ossification occurs subperiosteally and so is essentially intramembranous.…”
mentioning
confidence: 99%